2022
DOI: 10.1039/d2cp00667g
|View full text |Cite
|
Sign up to set email alerts
|

Collective movement and thermal stability of fullerene clusters on the graphene layer

Abstract: Understanding the motion characteristics of fullerene clusters on the graphene surface is critical for designing the surface manipulation systems. Toward this purpose, using molecular dynamics method, we evaluated six clusters...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…The Tersoff potential has shown accurate predictions in the simulation of graphene at high temperatures, such as the amplitude of surface ripples 34 and desorption temperature of the C60 molecule from graphene. 34,35 The nanocars were modeled by the Molecular Mechanics (MM) force field [36][37][38] as previously employed in other studies. [18][19][20][22][23][24] For this purpose, we considered two atom types for carbon atoms in the nanomachines.…”
Section: Methodsmentioning
confidence: 99%
“…The Tersoff potential has shown accurate predictions in the simulation of graphene at high temperatures, such as the amplitude of surface ripples 34 and desorption temperature of the C60 molecule from graphene. 34,35 The nanocars were modeled by the Molecular Mechanics (MM) force field [36][37][38] as previously employed in other studies. [18][19][20][22][23][24] For this purpose, we considered two atom types for carbon atoms in the nanomachines.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the motion of molecules on surfaces is of great importance in developing nano-transportation systems on the surface 1 . Using experimental and computational studies, many researchers have tried to understand the surface motion of various molecules in the past decade [2][3][4][5][6][7][8][9] . The experimental tools such as scanning tunneling microscopy (STM) require highly specialized equipment for investigating the surface phenomena at nanometer scale 10,11 .…”
mentioning
confidence: 99%
“…For designing surface manipulation systems, thermal stability and collective movement of six clusters of fullerenes were investigated by means of the MD method. 25 This study showed that as the number of fullerenes increases, they separate into large clusters at higher temperatures. In addition to the abovementioned studies, a number of reports have also reflected the properties of C 60 through MD methods.…”
Section: Introductionmentioning
confidence: 84%